Tax Compliance, Sales Growth, and the Existence of External Auditors: Evidence From Government Ownership Companies - Putri, Citradika Didha; Damayanti, Theresia Woro (Journal of Accounting and Finance, 2022)
This study aims to determine the effect of sales growth on tax compliance in terms of different aspects, namely, companies with government ownership. The presence of an external auditor becomes a moderating variable that will strengthen or weaken the effect of sales growth on tax compliance. The sample uses data from the World Bank Enterprise Surveys conducted by the World Bank in 2006-2018 in as many as 74 countries with 335 companies. This research is processed and analyzed using Ordered Logistic Regression (OLR). The results show that sales growth does not affect corporate tax compliance with government ownership. External auditors strengthen the influence of sales growth on tax compliance. This study complements and expands the literature on tax compliance on government ownership and has a broad scope using cross-country analysis.